50-74 years old people awareness on colon cancer prevention program - Gendvilaitė, Vilija (Slauga. Mokslas ir praktika, 2020)
Preventive program of colorectal cancer is designed to develop colorectal cancer screening in Lithuania, using effective methods of medical science and practice. The aim of this program – to determine more cases of colorectal cancer in the early stages and reduce death – rate of this oncological disease. The aim of research work: to evaluate the awareness of 50–74 years – old respondents about the colorectal cancer preventive program. Materials and methods. Methods of research – quantitative research: questionnaire. A questionnaire consisting of 29 questions was prepared by author to evaluate the awareness and motivation of 50–74 years – old respondents to participate in preventive program of colorectal cancer. 122 respondents in total participated in the research. All of them were from one health care institution of Šiauliai district. Results. 80 % of men and 82.3 % of women interviewed knew that the colorectal cancer early diagnostics program was being carried out. 50–74 years old people learned about this preventive program in most cases from family doctors (46.7 %) and information measures (43.4 %). Only (15.6%) respondents learned about this preventive program from nurses. Awareness of the colorectal cancer early diagnostics program is statistically significantly related to education (p = 0,014). More than half 50–74 years old people (60.7 %) were not taking part in this preventive program. Most of the respondents as the reason they were taking part in this preventive program indicated the taking care of their health (72.9 %). Reasons of not taking part in the program: lack of information (36.5 %); thinking about it but have not had time to get checked yet (35.1 %); not thinking about it (23.0 %).
Keywords: awareness; preventive programs; colorectal cancer